Static posturography in aging and Parkinson's disease - Ickenstein, Guntram W.; Ambach, Helmut; Kloeditz, Antonia; Koch, Horst; Isenmann, Stefan; Reichmann, Heinz; Ziemssen, Tjalf (Frontiers in Aging Neuroscience, 2012)
Introduction: In clinical practise, evaluation of postural control is based on the neurological examination, including Romberg’s test, examination of gait and performance of pull test as part of the Unified Parkinson´s Disease Rating Scale (UPDRS). The goal of our study was to identify posturographic parameters since quantitative technical methods for the measurement of postural control are not established in clinical routine yet. Methods: In this cross-sectional study design we examined patients with Parkinson's disease (Hoehn & Yahr <3; PD n=12) on a static posturographic platform (eyes open and eyes closed), performing a standard Romberg’s test during neurological examination and compared the results with an age-matched control group (healthy adult control; HAC n=10) and a healthy young control (HYC n=21). Results: In the platform Romberg’s test with open eyes, the patients with Parkinson’s disease (PD) showed a significantly greater mean sway (PD: 14.98 vs. HAC: 8.77 [mm], p<0.003 vs. HYC 7.80 [mm]), greater mean radius (PD: 28.31 vs. HAC: 16.36 [mm], p<0.008 vs. HYC: 14.19 [mm]) and greater marked area (PD: 2.38 vs. HAC: 0.88 [cm2], p<0.016 vs. HYC: 0.78 [cm2]) compared to the healthy adult control (HAC). The Romberg’s test with closed eyes revealed a significantly greater mean sway (PD: 13.83 vs. HAC: 10.12 [mm], p<0.033 vs. HYC: 5.82 [mm]) and greater mean radius (PD: 25.03 vs. HAC: 18.15 [mm], p<0.045 vs. HYC: 9.11 [mm]) compared to both groups. Conclusions: The platform Romberg test with closed eyes detected significant differences in elderly people and patients with Parkinson's disease, which could be objectively quantified with static posturography testing. Age alone showed significant changes, only detectable with closed eyes. Therefore balance testing with a new computerized approach could help to identify balance problems in a geriatric assessment in clinical routine, especially with the parameters marked area and mean sway.